Method for detecting content of polyacrylamide in salt solution
By performing a series of reactions in the aluminum salt solution, the problem of low detection accuracy in the prior art is solved, and the accurate determination of the content of flocculant in the aluminum salt solution is achieved.
Patent Information
- Application Number
- CN202411685289.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-21
AI Technical Summary
The prior art is difficult to accurately detect the content of polyacrylamide flocculants in aluminum salt solutions, and the detection accuracy is not high and inaccurate.
The content of polyacrylamide is finally determined by preparing a standard polyacrylamide solution of different concentrations and carrying out a series of reactions, including the addition of saturated bromine water, sodium formate solution, potassium fluoride solution and starch-cadmium iodide solution.
Accurate detection of the content of polyacrylamide flocculant in aluminum salt solution is achieved, and the detection results are high in precision, which is suitable for the determination of the lowest content of flocculant (about 1 ppm).
Smart Images

Figure CN119666768A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of analytical chemistry, and in particular to a method for detecting the content of polyacrylamide in a salt solution. Background Art
[0002] The "one-step acid dissolution" process is a fly ash hydrochloric acid method for extracting alumina independently developed by the Guoneng Junneng Group based on the coal resource advantages of the Jungar mining area. This process technology is to mix fly ash with hydrochloric acid for high-temperature reaction, and finally produce alumina products with a purity of up to 99.9% through processes such as dissolution, solid-liquid sedimentation separation, filtration control, resin impurity removal, evaporation crystallization and high-temperature roasting. However, the existing solid-liquid sedimentation separation process flocculant content detection cannot provide indicators sufficient to prove the flocculant residue in the feed liquid due to the lack of an effective and simple detection method. Therefore, it is of great significance to invent a method for quickly determining the content of polyacrylamide flocculants in aluminum salt solutions.
[0003] The prior art discloses a simple method for determining the flocculant content in sand and a detection device thereof. The detection device includes a U-tube, a photoelectric tube, a heating device, a micro electromagnetic pump and other structures. The detection device is used to respectively determine the viscosity of flocculant solutions of different concentrations, which are represented by the time interval between two scales. The corresponding relationship between the time interval value and the flocculant concentration is determined, and a fitting curve is drawn. Then the sand to be tested is weighed, dried, and sieved; the sand and water are mixed in proportion, stirred, and the supernatant is filtered; the viscosity of the supernatant is determined using the detection device; the concentration of the flocculant is obtained based on the corresponding relationship, and whether the flocculant content in the sand exceeds the standard is evaluated. This method is not suitable for detecting the content of polyacrylamide flocculants in aluminum salts.
[0004] The prior art discloses a method for detecting the residual amount of flocculant in machine-made sand, comprising the following steps: determining the total organic carbon content of tap water as TOC-0; using the tap water to prepare flocculant aqueous solutions of different concentrations, and determining the total organic carbon content of the flocculant aqueous solutions of different concentrations as TOCs; determining the relationship between TOCs of the flocculant aqueous solution and the flocculant concentration by least squares fitting (1): TOCs = TOC-0 + KC. Take the dried sand sample to be tested, mix it with tap water, wash it with clean water, dilute it with the sand washing water, and determine the total organic carbon content as TOC-(sample); substitute TOC-(sample) into formula (1) to calculate the residual amount of flocculant in the machine-made sand. This method cannot accurately detect the content of polyacrylamide flocculants in aluminum salts.
[0005] The content of polyacrylamide flocculants in aluminum salt solutions produced by the acid method is difficult to accurately detect due to the interference of impurity elements. The current detection method of polyacrylamide flocculants in aluminum salt solutions has certain limitations due to inconsistent matrix, different element types, content ranges, and uncertain interference factors, which affects the accuracy of the inspection. Therefore, it is of great significance to develop a complete set of analytical methods for the content of polyacrylamide flocculants in aluminum salt solutions. Summary of the invention
[0006] The main purpose of the present application is to provide a method for detecting the content of polyacrylamide in a salt solution, so as to solve the problem of low precision and inaccuracy in the detection of polyacrylamide flocculants in the prior art.
[0007] In order to achieve the above object, according to one aspect of the present application, a method for detecting the content of polyacrylamide in an aluminum salt solution is provided, comprising the following steps:
[0008] Step 1: Prepare polyacrylamide standard solutions of different concentrations;
[0009] Step 2: Add saturated bromine water to the polyacrylamide standard solution for reaction, then add sodium formate solution for reaction, and finally add starch-cadmium iodide solution for reaction, and measure the standard absorbance after color development; take the absorbance as the abscissa and the concentration of the polyacrylamide standard solution as the ordinate to obtain a standard curve;
[0010] Step 3: Add saturated bromine water to the test salt solution containing polyacrylamide for reaction, then add sodium formate solution for reaction, then add potassium fluoride solution for reaction, and finally add starch-cadmium iodide solution for reaction, and measure the actual absorbance after color development;
[0011] Step 4: Substitute the actual absorbance into the standard curve to obtain the polyacrylamide content in the salt solution to be tested.
[0012] Furthermore, the salt solution to be tested is an aluminum salt solution; and / or a buffer solution of sodium acetate is also added to the salt solution to be tested.
[0013] Furthermore, the volume ratio of the salt solution to be tested, saturated bromine water, sodium formate solution, potassium fluoride solution and starch-cadmium iodide solution in step 3 is (1-1.5): (1-1.5): (4-6): (4-7): (4-6); wherein the concentration of saturated bromine water is 3wt%-4wt%; the concentration of sodium formate solution is 1wt%-3wt%; and the concentration of potassium fluoride is 3wt%-6wt%;
[0014] Furthermore, the reaction time of adding saturated bromine water in step 3 is 15 to 30 minutes.
[0015] Furthermore, the reaction time of adding the sodium formate solution in step 3 is 5 to 20 minutes.
[0016] Furthermore, the reaction time of adding the potassium fluoride solution in step 3 is 10 to 15 minutes.
[0017] Furthermore, the reaction time of adding the starch-cadmium iodide solution in step 3 is 5 to 40 minutes.
[0018] Furthermore, the reaction time of adding saturated bromine water in step 3 is 13 to 17 minutes, preferably 14 to 16 minutes.
[0019] Furthermore, the reaction time of adding the sodium formate solution in step 3 is 5 to 15 minutes, preferably 9 to 11 minutes.
[0020] Furthermore, the reaction time of adding the potassium fluoride solution in step 3 is 5 to 15 minutes, preferably 9 to 11 minutes.
[0021] Furthermore, the reaction time of adding the starch-cadmium iodide solution in step 3 is 10 to 20 minutes.
[0022] Furthermore, the volume ratio of the polyacrylamide standard solution, saturated bromine water, sodium formate solution and starch-cadmium iodide solution in step 2 is (1-1.5):(1-1.5):(4-6):(4-6); wherein the concentration of saturated bromine water is 3wt%-4wt%; and the concentration of sodium formate solution is 1wt%-3wt%.
[0023] Furthermore, the reaction time of adding saturated bromine water in step 2 is 15 to 30 minutes.
[0024] Furthermore, the reaction time of adding the sodium formate solution in step 2 is 5 to 20 minutes.
[0025] Furthermore, the reaction time of adding the starch-cadmium iodide solution in step 2 is 5 to 40 minutes.
[0026] Furthermore, the concentration of the polyacrylamide standard solution in step 1 is 90-110 mg / L.
[0027] Furthermore, the formula of the standard curve is C=3.6073A-0.096; wherein C is the concentration of polyacrylamide, in mg / L; and A is the corresponding absorbance value.
[0028] Furthermore, the test wavelength of the standard absorbance and the actual absorbance is 590 nm.
[0029] Furthermore, the detection limit of the detection method is 1.5 mg / L, and the lower limit of determination is 5 mg / L.
[0030] By applying the technical solution of the present application, a method for detecting the content of polyacrylamide flocculants in aluminum salt solutions is provided, which can simultaneously detect the flocculant content in aluminum-based materials and is suitable for the determination of the minimum flocculant content (about 1 ppm). The detection results have high precision and good stability during the instrument detection process. The detection method is of great significance for the qualitative characterization of enterprise product quality and provides technical support for the detection of flocculant residues in acid-process alumina production. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] The drawings constituting part of the present application are used to provide a further understanding of the present application. The exemplary embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:
[0032] Figure 1 The standard curve diagram of the polymer concentration determined by the starch-cadmium iodide method in Example 1 of the present application is shown;
[0033] Figure 2 The optimized curve diagram of the amount of potassium fluoride solution added in Example 1 of the present application is shown;
[0034] Figure 3 The optimized time curve after adding the potassium fluoride solution in Example 1 of the present application is shown;
[0035] Figure 4 The time optimization curve after adding sodium formate solution in Example 1 of the present application is shown;
[0036] Figure 5 The time optimization curve diagram after adding starch-cadmium iodide solution in Example 1 of the present application is shown;
[0037] Figure 6 The time optimization curve after adding bromine water in Example 1 of the present application is shown. DETAILED DESCRIPTION
[0038] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present application will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0039] According to one aspect of the present application, a method for detecting the content of polyacrylamide flocculant in an aluminum salt solution is provided, comprising the following steps:
[0040] Step 1: Prepare polyacrylamide standard solutions of different concentrations;
[0041] Step 2: Add saturated bromine water to the polyacrylamide standard solution for reaction, then add sodium formate solution for reaction, and finally add starch-cadmium iodide solution for reaction, and measure the standard absorbance after color development; take the absorbance as the abscissa and the concentration of the polyacrylamide standard solution as the ordinate to obtain a standard curve;
[0042] Step 3: Add saturated bromine water to the test salt solution containing polyacrylamide for reaction, then add sodium formate solution for reaction, then add potassium fluoride solution for reaction, and finally add starch-cadmium iodide solution for reaction, and measure the actual absorbance after color development;
[0043] Step 4: Substitute the actual absorbance into the standard curve to obtain the polyacrylamide content in the salt solution to be tested.
[0044] The method provided in the present application for rapidly determining the content of polyacrylamide flocculants in aluminum salt solutions comprises pre-treating the sample and then adding a certain amount of Br to the material to be tested. 2 , and the amide group in the flocculant undergoes a substitution reaction to generate bromoamide, and sodium formate is added to reduce the excess Br 2 . Then add a certain amount of starch-cadmium iodide solution, which undergoes a redox reaction with bromoamide to generate iodine elemental color. At a wavelength of 590nm, the time-scan absorbance of the spectrophotometer is linearly related to the flocculant concentration in the test liquid, thereby obtaining the flocculant content. This method has high detection efficiency and good accuracy, and can realize the determination of flocculant content in aluminum salt samples, providing technical support for the analysis and detection of flocculant content in the alumina production process. It greatly improves the sensitivity and accuracy of the detection, and ensures the efficiency and credibility of the detection process. At the same time, it provides a data basis for further exploring the potential characteristics of flocculants and exploring the flocculation mechanism. This method is suitable for the detection of flocculant content in a mixed system of polyacrylamide flocculants and high-salt solid-liquid mixtures. The operation method is simple and easy, and the test results have good repeatability.
[0045] The method for detecting the content of polyacrylamide flocculants in the above-mentioned aluminum salt solution provided in the present application can simultaneously detect the content of flocculants in aluminum-based materials, is suitable for the determination of the minimum content of flocculants (about 1 ppm), and has high precision of the detection results and good stability during the instrument detection process. The detection method is of great significance for the qualitative characterization of enterprise product quality, and at the same time provides technical support for the detection of flocculant residues in acid-process alumina production.
[0046] In some embodiments, the salt solution to be tested is an aluminum salt solution; a buffer solution of sodium acetate is also added to the salt solution to be tested.
[0047] In some embodiments, the volume ratio of the test salt solution, saturated bromine water, sodium formate solution, potassium fluoride solution and starch-cadmium iodide solution in step 3 is (1-1.5): (1-1.5): (4-6): (4-7): (4-6); the volume ratio is, for example, 1:1:5:5:5; wherein the concentration of saturated bromine water is 3wt%-4wt%; the concentration of sodium formate solution is 1wt%-3wt%; for example, 1wt%; the concentration of potassium fluoride is 3wt%-6wt%; for example, 3wt%.
[0048] The present application can fully react and improve detection accuracy through the volume ratio and concentration of the above-mentioned substances.
[0049] In some embodiments, the reaction time of adding saturated bromine water in step 3 is 15 to 30 min; further 13 to 17 min; further 14 to 16 min; for example 15 min.
[0050] The present application limits the residence time or reaction time of saturated bromine water, so that the bromine water and the amide groups in the polyacrylamide can fully undergo substitution reaction to generate bromoamide.
[0051] In some embodiments, the reaction time of adding the sodium formate solution in step 3 is 5 to 20 minutes; further 5 to 15 minutes; further 9 to 11 minutes; for example 10 minutes.
[0052] The present application can fully reduce excess bromine water by limiting the residence time or reaction time of sodium formate.
[0053] In some embodiments, the reaction time of adding potassium fluoride solution in step 3 is 10 to 15 minutes; further 10 to 12 minutes; further 9 to 11 minutes; for example 10 minutes.
[0054] The present application can eliminate dry metal ions in the flocculant and improve the detection accuracy by limiting the residence time or reaction time of potassium fluoride.
[0055] In some embodiments, the reaction time of adding starch-cadmium iodide solution in step 3 is 5 to 40 min; further 10 to 20 min; for example 20 min.
[0056] The present application limits the residence time of the starch-cadmium iodide solution so that the redox reaction can fully occur and the color development is stable.
[0057] In some embodiments, the volume ratio of the polyacrylamide standard solution, saturated bromine water, sodium formate solution and starch-cadmium iodide solution in step 2 is (1-1.5): (1-1.5): (4-6): (4-6); the volume ratio is, for example, 1:1:5:5; wherein the concentration of saturated bromine water is 3wt%-4wt%; the concentration of sodium formate solution is 1wt%-3wt%, for example, 1wt%.
[0058] In some embodiments, the reaction time of adding saturated bromine water in step 2 is 15 to 30 min; further 13 to 17 min; further 14 to 16 min; for example 15 min.
[0059] The present application limits the residence time or reaction time of saturated bromine water, so that the bromine water and the amide groups in the polyacrylamide can fully undergo substitution reaction to generate bromoamide.
[0060] In some embodiments, the reaction time of adding the sodium formate solution in step 2 is 5 to 20 minutes; further 5 to 15 minutes; further 9 to 11 minutes; for example 10 minutes.
[0061] The present application can fully reduce excess bromine water by limiting the residence time or reaction time of sodium formate.
[0062] In some embodiments, the reaction time of adding starch-cadmium iodide solution in step 2 is 5 to 40 min; further 10 to 20 min; for example 20 min.
[0063] The present application limits the residence time of the starch-cadmium iodide solution so that the redox reaction can fully occur and the color development is stable.
[0064] In some embodiments, the concentration of the polyacrylamide standard solution in step 1 is 90-110 mg / L, preferably 100 mg / L.
[0065] In some embodiments, the formula of the standard curve is C=3.6073A-0.096; wherein C is the concentration of polyacrylamide, in mg / L; and A is the corresponding absorbance value.
[0066] In some embodiments, the test wavelength of the standard absorbance and the actual absorbance is 590 nm.
[0067] In some embodiments, the detection limit of the detection method is 1.5 mg / L and the lower limit of determination is 5 mg / L.
[0068] The present application also provides a more specific method for rapidly determining the content of polyacrylamide flocculants in aluminum salt solutions, comprising:
[0069] The sample is first pretreated, including masking, oxidation, and substitution reaction treatment; standard solution preparation, matrix solution preparation, working curve preparation, and finally a series of standard solutions and samples are measured using a spectrophotometer. The specific measurement steps are as follows:
[0070] 1) Prepare reagents: including sodium formate solution, sodium acetate buffer solution, potassium fluoride solution as masking agent, saturated bromine water, starch-cadmium iodide solution, high-purity aluminum wire, and distilled water;
[0071] 2) Prepare standard solution
[0072] Take an appropriate amount of polyacrylamide, dry it at 50℃ for 1h, accurately weigh 0.030g of polyacrylamide, put it into a beaker containing 300ml deionized water on a magnetic stirrer, stir and dissolve it for 3h, then put it into a 500ml volumetric flask, shake well, dilute to the mark, and transfer it to a brown reagent bottle for later use;
[0073] 3) Sample pretreatment: take 1 ml of sample into a 50 ml volumetric flask, add 5.0 ml of potassium fluoride solution (3 wt%), the residence time after potassium fluoride is added is selected as 10 min masking time; the neutralization reaction time of sodium formate (1 wt%) and excess bromine water is selected as 10 min; the starch-cadmium iodide oxidation-reduction time is selected as 20 min; the bromine water substitution reaction time is selected as 15 min; the saturated bromine water (3% to 4 wt%) substitution reaction time is selected as 15 min.
[0074] 4) Preparation of internal working curve
[0075] Accurately pipette 0, 0.3ml, 0.5ml, 0.8ml, 1.0ml, 1.5ml, 2.0ml, 2.5ml, 3.0ml of the above polyacrylamide standard solution into 9 50ml volumetric flasks, add 5ml of sodium acetate buffer solution, add about 30ml of deionized water, and then add 1ml of bromine water. After shaking and reacting for 15min, continue to add 5ml of 1wt% sodium formate solution. After shaking and reacting for 10min, continue to add 5ml of starch-cadmium iodide solution, shake well, dilute to the scale, and color for 15min. Measure the absorbance at 590nm and draw a standard curve;
[0076] 5) Determination: The starch-cadmium iodide method was used to determine the 9 standard solutions. The absorbance value was used as the horizontal coordinate and the polymer content was used as the vertical coordinate to draw a standard curve. The internal standard method standard curve of each element was obtained. The intersection of the curve and the horizontal axis was the concentration of the element to be measured in the sample. Multiplying it by the corresponding dilution multiple, the content of the element to be measured in the sample was obtained;
[0077] (6) Main instruments and working conditions:
[0078] Spectrophotometer: NexION TMModel 300, Thermo Fisher Scientific Inc., USA; Electronic balance: Model ME204E, sensitivity 0.0001g, Mettler Toledo Measurement Technology Co., Ltd., Switzerland;
[0079] (7) In step 4): take 1-1.5 ml of the sample to be tested into a 50 ml volumetric flask, add 4.0-7.0 ml of potassium fluoride solution (3 wt%-6 wt%, the residence time after potassium fluoride is added is selected as 10-15 min masking time; the neutralization reaction time of sodium formate (1-3 wt%) and excess bromine water is selected as 5-20 min; the redox time of starch-cadmium iodide is selected as 5-40 min; the substitution reaction time of saturated bromine water (3%-4 wt%) is selected as 15-30 min.
[0080] (8) Detection limit: Under the experimental instrument conditions of this application, an aluminum salt solution without flocculant was used as a blank for 11 consecutive measurements. The detection limit of this method was 3 times the standard deviation of the measurement result, and 10 times the standard deviation was used as the detection limit of this method: 1.5 mg / L; the lower limit of determination was 5 mg / L.
[0081] (9) Precision: After the spectrophotometer was preheated for 60 min, the measurement was repeated 11 times with flocculant solutions at concentrations of 20, 30, 40, and 50 mg / L, and the relative standard deviation was ≤5.0%;
[0082] (10) Recovery rate experiment: The recovery rate of the flocculant content in the aluminum salt solution sample was 86.67% to 99.17%, which fully meets the requirements of the analytical method;
[0083] Stability: After the spectrophotometer was preheated for 60 minutes, a flocculant solution with a concentration of 20 mg / L was used to measure once every 10 minutes within 2 hours, for a total of 11 times, the relative standard deviation was ≤5%, and the linear correlation coefficient of the working curve was R≥0.9989.
[0084] The above-mentioned detection method for rapid determination of polyacrylamide flocculant content in aluminum salt solution provided in the present application is that the sample is first pre-treated, including masking, oxidation, and substitution reaction treatment. Standard solution preparation, matrix solution preparation, working curve preparation, and finally the series of standard solutions and samples are measured by spectrophotometer; the best sample measurement conditions are established to provide technical support for the analysis of heavy metal elements in aluminum-based alumina produced by the acid method.
[0085] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0086] The raw materials used in the examples of this application are prior art and can be purchased commercially.
[0087] Example 1
[0088] 1. Reagent preparation and calibration
[0089] 1. Starch-cadmium iodide solution: accurately weigh 5.50g of cadmium iodide, dissolve it in 150ml of deionized water, heat and boil for 10min, cool to room temperature, add 1.250g of soluble starch, stir and boil for 5min, filter with a Buchner funnel (slow filter paper) after dissolution, place in a 500ml volumetric flask, shake well, dilute to the mark, transfer to a brown reagent bottle for later use.
[0090] 2. Sodium formate solution (1%): Accurately weigh 5.00 g of sodium formate, place it in a 500 ml volumetric flask, shake well, and dilute to the mark.
[0091] 3. Buffer solution: Accurately weigh 12.50 g of sodium acetate, dissolve it in 400 ml of deionized water, add 0.250 g of aluminum sulfate 18hydrate, adjust the pH value to 4.00 with glacial acetic acid, place it in a 500 ml volumetric flask, shake well, and dilute to the mark.
[0092] 4. Potassium fluoride solution (3%): Accurately weigh 4.860 g of potassium fluoride dihydrate, place it on an electronic balance, add deionized water until the balance reads 100.00 g, stir to dissolve all the solids, and transfer to a reagent bottle for later use.
[0093] 5. Saturated bromine water: saturated bromine water (3% ~ 4wt%).
[0094] 6. Polyacrylamide standard solution (100 mg / L): Take an appropriate amount of polyacrylamide, dry it at 50℃ for 1h, accurately weigh 0.030g of polyacrylamide, put it into a beaker containing 300ml deionized water on a magnetic stirrer, stir and dissolve it for 3h, then put it into a 500ml volumetric flask, shake well, dilute to the scale, and transfer it to a brown reagent bottle for later use.
[0095] 2. Analysis steps
[0096] Accurately transfer 1 ml of the test solution to a 50 ml volumetric flask, add 5 ml of buffer solution, add about 30 ml of deionized water, and then add 1 ml of bromine water. After shaking for 15 minutes, add 5 ml of 1% sodium formate solution, shake for 10 minutes, and then add 5 ml of potassium fluoride solution (3%). After shaking for 10 minutes, add 5 ml of starch-cadmium iodide solution, shake, dilute to the mark, and color for 15 minutes. Measure the concentration of polyamide in the liquid at 590 nm.
[0097] 3. Results and Methods
[0098]
[0099] Where:
[0100] C—spectrophotometer reading, mg / L;
[0101] k—dilution multiple;
[0102] V—sampling volume, mL
[0103] 3.1 Accurately pipette the above polyacrylamide standard solution
[0104] 0, 0.3ml, 0.5ml, 0.8ml, 1.0ml, 1.5ml, 2.0ml, 2.5ml, 3.0ml were placed in 9 50ml volumetric flasks, 5ml buffer solution was added, about 30ml deionized water was added, and 1ml bromine water was added. After shaking for 15min, 5ml 1% sodium formate solution was added. After shaking for 10min, 5ml starch-cadmium iodide solution was added, shaken, fixed to scale, and color developed for 15min. The 9 standard solutions were measured by starch-cadmium iodide method, and the absorbance was measured at 590nm. The standard curve was drawn with the absorbance value as the horizontal axis and the polymer content as the vertical axis.
[0105] Draw the standard curve Figure 1 , we get the following formula:
[0106] C = 3.6073A-0.096;
[0107] Where: C is the polymer concentration, mg / L; A is the absorbance value.
[0108] The test results showed good linearity in the range of 0-300 mg / L, with a correlation coefficient of R2=0.9982.
[0109] 3.2 Experimental study on interference factors in the process of flocculant content detection
[0110] Fe 3+ It will oxidize I- into elemental iodine, which will darken the color of the test solution, increase the absorbance, and produce a large positive error. Fe can be masked by adding a certain amount of potassium fluoride solution. 3+ , thereby eliminating this interference. The addition of potassium fluoride solution will react with the Al in the test solution. 3+ , Fe 3+ , Ca 2+ The contents of the components in the feed liquid are shown in Table 1.
[0111] 2Fe 3+ +2I - →2Fe 2+ +I 2
[0112] Al 3+ +6F -→[AlF 6 ] 3-
[0113] Fe 3+ +6F - →[FeF 6 ] 3-
[0114] Ca 2+ +2F - →CaF 2 ↓
[0115] Take 1 ml of aluminum salt solution (without polyacrylamide) in a 50 ml volumetric flask, adjust the amount of potassium fluoride solution (3%), keep other conditions unchanged, and test the absorbance. The test results are shown in Table 2.
[0116] According to the experimental results, when 4.0 ml of potassium fluoride solution (3 wt%) is added, the absorbance approaches 0. However, in order to adapt to the concentration fluctuation of interfering ions in the feed solution, 5.0 ml is more appropriate and no precipitation is produced. Figure 2 shown.
[0117] 3.3 Experimental study on optimization of color development time after adding potassium fluoride solution (3wt%)
[0118] Prepare an aluminum salt solution containing polyacrylamide at a concentration of 20-40 ppm. Accurately pipette 1 ml into a 50 ml volumetric flask, adjust the residence time after adding the potassium fluoride solution, keep other conditions unchanged, and test the concentration. The results are shown in Table 3.
[0119] It can be seen from Table 3 that the test errors of the optimized color development time of 5min and 15min are relatively large. The test error of the residence time of 10min after the addition of potassium fluoride is the smallest, which is close to the true value. Therefore, the color development time of 10min is selected. Figure 3 shown.
[0120] 1) Experimental study on time optimization after adding sodium formate solution
[0121] Prepare an aluminum salt solution containing polyacrylamide at a concentration of 20-40ppm. Accurately pipette 1ml into a 50ml volumetric flask, adjust the waiting time after adding the sodium formate solution, keep other conditions unchanged, and test the concentration. The results are shown in Table 4.
[0122] From Table 4, it can be seen that the test errors of the neutralization reaction time of 5min and 15min are relatively large, and the test error of the neutralization reaction time of sodium formate and excess bromine water of 10min is the smallest, which is close to the true value. Therefore, 10min is selected as the reaction time. Figure 4 shown.
[0123] 2) Experimental study on color development time after adding starch-cadmium iodide solution
[0124] Prepare an aluminum salt solution containing polyacrylamide at a concentration of 20-40ppm; accurately transfer 1ml to a 50ml volumetric flask, adjust the waiting time after adding the starch-cadmium iodide solution, keep other conditions unchanged, and test the concentration. The results are shown in Table 5.
[0125] It can be seen from Table 5 that the reaction time of the brominated product and cadmium iodide is 5min and 10min, the test error is large, and the test error of the 20min redox time is the smallest, which is close to the true value. Therefore, 20min is selected as the reaction time. Figure 5 shown.
[0126] 3) Experimental study on optimization of bromine substitution reaction time
[0127] Prepare aluminum solution containing polyacrylamide at a concentration of 20-40ppm. Accurately pipette 1ml into a 50ml volumetric flask, adjust the waiting time after adding bromine water, keep other conditions unchanged, and test the concentration. The results are shown in Table 6.
[0128] From Table 6, we can see that the test errors of bromine water substitution reaction time of 5min, 10min, and 20min are relatively large, and the test error of 15min substitution reaction time is the smallest, which is close to the true value. Therefore, 15min is selected as the reaction time. Figure 6 shown.
[0129] (10) Detection limit: Under the experimental instrument conditions of this application, an aluminum salt solution without flocculant was used as a blank and the detection limit of the method was 1.5 mg / L. The lower limit of determination was 5 mg / L.
[0130] (9) Precision: After the spectrophotometer was preheated for 60 min, the measurement was repeated 11 times with flocculant solutions at concentrations of 20, 30, and 40 mg / L, and the relative standard deviation was ≤5.0%;
[0131] (10) Recovery rate experiment: The recovery rate of the flocculant content in the aluminum salt solution sample was 86.67% to 99.17%, which fully meets the requirements of the analytical method;
[0132] The stability test results of the method of the present application are shown in Table 7; the detection limit and the lower limit of determination results are shown in Table 8; the recovery rate determination results are shown in Table 9; and the precision test results of the method of the present application are shown in Table 10.
[0133] Table 1 Analysis results of aluminum salt material properties
[0134] Aluminum Chloride Full Iron <![CDATA[Fe 2+ ]]> <![CDATA[Ca 2+ ]]> 220±20g / L 4.0-5.0g / L 1.5-2.0g / L 8.0-10.0g / L
[0135] Table 2 Results of optimization experiment on the amount of potassium fluoride solution added
[0136]
[0137]
[0138] Table 3 Potassium fluoride solution added after time optimization experimental results
[0139]
[0140] Table 4 Time optimization experimental results after adding sodium formate solution
[0141]
[0142] Table 5 Time optimization experimental results after adding starch-cadmium iodide solution
[0143]
[0144]
[0145] Table 6 Time optimization experimental results after adding bromine water
[0146]
[0147] Table 7 Stability test results of the test method
[0148] serial number Flocculant test results (mg / L) 1 20.33 2 20.9 3 20.87 4 21.35 5 21.56 6 21.98 7 20.11 8 20.98 9 20.37 10 21.89 11 21.62 average value 21.09 Standard Deviation 0.64
[0149] Table 8 Detection limit and lower limit of determination of the determination method (mg / L)
[0150]
[0151]
[0152] Table 9 Spike recovery test (%)
[0153]
[0154] Table 10 Precision test results of the test method
[0155]
[0156]
[0157]
[0158] The method for detecting the content of polyacrylamide flocculants in the above-mentioned aluminum salt solution provided in the present application can simultaneously detect the content of flocculants in aluminum-based materials, and is suitable for the determination of the minimum content of flocculants (about 1 ppm), and the detection results have high precision, with a detection limit of 1.5 mg / L and a determination lower limit of 5 mg / L; the instrument has good stability during the detection process; the detection method provides technical support for the qualitative characterization of product quality and the detection of flocculant residues in acid-process alumina production.
[0159] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0160] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for detecting the content of polyacrylamide in a saline solution, characterized in that: The method comprises: Step 1: Prepare polyacrylamide standard solutions of different concentrations; Step 2: adding saturated bromine water to the polyacrylamide standard solution for reaction, then adding sodium formate solution for reaction, and finally adding starch-cadmium iodide solution for reaction, and measuring the standard absorbance after color development; taking the absorbance as the abscissa and the concentration of the polyacrylamide standard solution as the ordinate to obtain a standard curve; Step 3: Add saturated bromine water to the test salt solution containing polyacrylamide for reaction, then add sodium formate solution for reaction, then add potassium fluoride solution for reaction, and finally add starch-cadmium iodide solution for reaction, and measure the actual absorbance after color development; Step 4: Substitute the actual absorbance into the standard curve to obtain the polyacrylamide content in the salt solution to be tested.
2. The method for detecting the content of polyacrylamide in a saline solution according to claim 1, characterized in that: The salt solution to be tested is an aluminum salt solution; and / or a buffer solution of sodium acetate is also added to the salt solution to be tested.
3. The method for detecting the content of polyacrylamide in a saline solution according to claim 1, characterized in that: The volume ratio of the test salt solution, the saturated bromine water, the sodium formate solution, the potassium fluoride solution and the starch-cadmium iodide solution in step 3 is (1-1.5): (1-1.5): (4-6): (4-7): (4-6); Wherein, the concentration of the saturated bromine water is 3wt% to 4wt%; the concentration of the sodium formate solution is 1wt% to 3wt%; and the concentration of the potassium fluoride is 3wt% to 6wt%.
4. The method for detecting the content of polyacrylamide in a saline solution according to any one of claims 1 to 3, characterized in that: The reaction time of adding the saturated bromine water in step 3 is 15 to 30 minutes; And / or, the reaction time of adding the sodium formate solution in step 3 is 5 to 20 minutes; And / or, the reaction time of adding the potassium fluoride solution in step 3 is 10 to 15 minutes; And / or, the reaction time of adding the starch-cadmium iodide solution in step 3 is 5 to 40 minutes.
5. The method for detecting the content of polyacrylamide in a saline solution according to any one of claims 1 to 3, characterized in that: The reaction time of adding the saturated bromine water in step 3 is 13 to 17 minutes; And / or, the reaction time of adding the sodium formate solution in step 3 is 5 to 15 minutes; And / or, the reaction time of adding the potassium fluoride solution in step 3 is 10 to 12 minutes; And / or, the reaction time of adding the starch-cadmium iodide solution in step 3 is 10 to 20 minutes.
6. The method for detecting the content of polyacrylamide in a saline solution according to any one of claims 1 to 5, characterized in that: The volume ratio of the polyacrylamide standard solution, the saturated bromine water, the sodium formate solution and the starch-cadmium iodide solution in step 2 is (1-1.5):(1-1.5):(4-6):(4-6); Wherein, the concentration of the saturated bromine water is 3wt% to 4wt%; the concentration of the sodium formate solution is 1wt% to 3wt%.
7. The method for detecting the content of polyacrylamide in a saline solution according to any one of claims 1 to 6, characterized in that: The reaction time of adding the saturated bromine water in step 2 is 15 to 30 minutes; And / or, the reaction time of adding the sodium formate solution in step 2 is 5 to 20 minutes; And / or, the reaction time of adding the starch-cadmium iodide solution in step 3 is 5 to 40 minutes.
8. The method for detecting the content of polyacrylamide in a saline solution according to any one of claims 1 to 7, characterized in that: The concentration of the polyacrylamide standard solution in step 1 is 90-110 mg / L; And / or, the formula of the standard curve is C=3.6073A-0.096; Wherein, C is the concentration of the polyacrylamide standard solution, in mg / L; A is the corresponding absorbance value.
9. The method for detecting the content of polyacrylamide in a saline solution according to claim 1, characterized in that: The test wavelength of the standard absorbance and the actual absorbance is 590 nm.
10. The method for detecting the content of polyacrylamide in a saline solution according to claim 1, characterized in that: The detection method has a detection limit of 1.5 mg / L for the polyacrylamide in the salt solution and a lower limit of 5 mg / L.